Nutritional status of rural school-going children (11-13 years) of Dharmapuri district, Tamil Nadu, South India - Elangovan, Prasanth; A. S., Hema Priya; Singaram, Kalpana (International Journal Of Community Medicine And Public Health, 2023)
Background: The childhood years are characterized by rapid growth and development on both a physical and mental level. Compared to adults, they require a greater amount of nutrition per unit of body weight. The prevalence of undernutrition among schoolchildren is one of the foremost public health problems in developing countries such as India. Various studies have highlighted the burden of undernutrition nationwide among different groups in India. The objective of the present study was to assess the nutritional status of school children attending schools in Dharmapuri, Tamil Nadu. Methods: A descriptive cross-sectional study was carried out among 972 school children of 11 to 13 years of age for 6 months by consecutive sampling technique. The children were assessed for nutritional status by clinical examination as well as anthropometric assessment and were compared with the WHO growth standards. Statistical analysis was conducted using SPSS version 22 on the data obtained. Results: The mean age of the children was 12.11±0.8 of which 491(51%) were boys and 481 (49%) were girls. Among children, the prevalence of underweight, overweight, and obesity was 565 (58%), 25 (2.6%), and 23 (2.4%) respectively. Conclusions: The burden of undernutrition is indeed a serious concern in the rural school children of Dharmapuri district in Tamilnadu. The importance of routine school health visits is stressed and this issue needs to be addressed promptly through a multipronged approach.